RHEUMATIC DISEASES IN THE ADULT POPULATION IN FEDERAL DISTRICTS OF RUSSIA - Rimma M Balabanova; Sh F Erdes (Научно-практическая ревматология)
Analysis of the official statistics of the Ministry of Health of the Russian Federation for the year 2011 indicates a growing incidence of diseases of the musculoskeletal system in adult population of Russia as compared to 2010. A total of 16,277 thousand of adult patients with this pathology were registered in 2011 (13958.4 per 100 thousand population), 3,673 thousand of them were newly diagnosed (3149.9 per 100 thousand). The distribution of the major rheumatic diseases over eight federal districts was studied. Significant differences in the overall and primary morbidity were observed in the federal regions.